Equality Impact Assessment Record : Energy Efficient Scotland : the Energy Efficiency (Private Rented Property) (Scotland) Regulations 2019 and Association Guidance.: Energy Efficient Scotland : the Energy Efficiency (Private Rented Property) (Scotland) Regulations 2019 and Association Guidance. (2019) - Unknown
No abstract available